Rock-climbing in the English Lake District : Third Edition - Jones, Owen Glynne, 1867-1899 (Salt Lake City, UT : Project Gutenberg, 2017)
"Rock-climbing in the English Lake District" by Owen Glynne Jones is a specialized guide on rock climbing, likely written in the late 19th century. The book documents various climbing routes and techniques within the picturesque but challenging terrain of the English Lake District. It also features illustrations and practical insights, reflecting the author$1 (Bs personal experiences and his dedication to the sport of mountaineering. The opening of the book introduces readers to the author, Owen Glynne Jones, detailing his early life, educational background, and burgeoning passion for climbing, particularly in the Welsh mountains and the Lake District. The memoir sets the stage for a journey through climbers' lore, where Jones displays his enthusiasm for the sport and the captivating landscapes of Britain$1 (Bs mountainous regions. There is an emphasis on personal anecdotes and interactions with fellow climbers, establishing a narrative that blends practical climbing insights with engaging storytelling, indicating that readers can expect both technical detail and an exploration of the climber's spirit. (This is an automatically generated summary.)s
Release date is 2017-11-24
E-text prepared by Anita Hammond, Wayne Hammond, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Mountaineering; Rock climbing -- England -- Lake District; Lake District (England) -- Description and travel